Do and die : the Chittagong uprising, 1930-34 - Chatterjee, Manini, 1961- (New Delhi ; New York : Penguin Books, 1999)
On the role of the young revolutionaries from Chattagram District, now in Bangladesh, in the freedom struggle of India.
Includes bibliographical references (p. [341]-345) and index.
Keywords: Chattagram District (Bangladesh) -- Politics and government